Love, Hatred And Death Reflected In Romeo And Juliet Movie Directed By Bazman Luhrmann (1996) : A Dynamic Structuralist Approach. - Lactea, Ariejaya Awan; , Prof. Dr. C. Bakdi Sumanto; , Drs. Abdillah Nugroho, M. Hum (2014)
The objective of this study is to analyze love, hatred & death and also to find out moral values in Romeo and Juliet movie directed by Bazman Luhrmann (1996). The film being investigated is inspired by Romeo and Juliet drama written by the famous English writer namely William Shakespeare. The research methodology being employed in this thesis is the Qualitative Research. During this research, the researcher watches Romeo and Juliet movie directed by Bazman Luhrmann (1996) to get the detailed information coming from the movie which consists of love, hatred and death reflected in Romeo and Juliet movie and analyzes the character in the movie. The researchers also analyses the important role of love, hatred and death and the changing of the characters attitude caused by love, hatred and death reflected in Romeo and Juliet movie directed by Bazman Luhrmann (1996) based on Kernodle‟s principle. According to Kernodle every play has six possible values, and all six may help in different ways to give the play organization and unity. Kernodle also explains that structure consists of plot, character, theme and texture consists of dialogue, mood, spectacle. Theoretical Approach being used in this thesis is the theory based on the dynamic structuralist approach. First the researcher investigates how are love, hatred & death reflected in Romeo and Juliet movie. The second is what kinds of moral value are reflected in Romeo and Juliet movie.